Ataxia telangiectasia gene mutations in leukaemia and lymphoma. - Boultwood, J (2001)
Ataxia telangiectasia (AT) is a rare multisystem, autosomal, recessive disease characterised by neuronal degeneration, genome instability, and an increased risk of cancer. Approximately 10% of AT homozygotes develop cancer, mostly of the lymphoid system. Lymphoid malignancies in patients with AT are of both B cell and T cell origin, and include Hodgkin's lymphoma, non-Hodgkin's lymphoma, and several forms of leukaemia. The AT locus was mapped to the chromosomal region 11q22-23 using genetic linkage analysis in the late 1980s and the causative gene was identified by positional cloning several years later. The ATM gene encodes a large protein that belongs to a family of kinases possessing a highly conserved C-terminal kinase domain related to the phosphatidylinositol 3-kinase domain. Members of this kinase family have been shown to function in DNA repair and cell cycle checkpoint control following DNA damage. Recent studies indicate that ATM is activated primarily in response to double strand breaks and may be considered a caretaker of the genome. Most mutations in ATM result in truncation and destabilisation of the protein, but certain missense and splicing errors have been shown to produce a less severe phenotype. AT heterozygotes have a slightly increased risk of breast cancer. Atm deficient mice exhibit many of the symptoms found in patients with AT and have a high frequency of thymic lymphoma. The association between mutation of the ATM gene and a high incidence of lymphoid malignancy in patients with AT, together with the development of lymphoma in Atm deficient mice, supports the proposal that inactivation of the ATM gene may be of importance in the pathogenesis of sporadic lymphoid malignancy. Loss of heterozygosity at 11q22-23 (the location of the ATM gene) is a common event in lymphoid malignancy. Frequent inactivating mutations of the ATM gene have been reported in patients with rare sporadic T cell prolymphocytic leukaemia (T-PLL), B cell chronic lymphocytic leukaemia (B-CLL), and most recently, mantle cell lymphoma (MCL). In contrast to the ATM mutation pattern in AT, the most frequent nucleotide changes in these sporadic lymphoid malignancies were missense mutations. The presence of inactivating mutations, together with the deletion of the normal copy of the ATM gene in some patients with T-PLL, B-CLL, and MCL, establishes somatic inactivation of the ATM gene in the pathogenesis of lymphoid malignancies, and strongly suggests that ATM functions as a tumour suppressor. The presence of missense mutations in the germline of patients with B-CLL has been reported, suggesting that some patients with B-CLL may be constitutional AT heterozygotes. The putative hereditary predisposition of B-CLL, although intriguing, warrants further investigation.